Through thickness changes to stiffness and thermal conductivity in thermal barrier coatings subjected to gradient exposure. Issue 9 (August 2023) - Lal, Devi; Saputo, John; Gildersleeve V, Edward J.; Sampath, Sanjay
Abstract: Sintering-induced increases in the elastic modulus and thermal conductivity of thermally sprayed Thermal Barrier Coatings (TBCs) under constraint by a bond-coated substrate due to thermal gradient exposure have been measured. The results suggest the degree of sintering due to this constrained thermal exposure to be significantly lower when compared to free standing exposed specimens. Overall, a ∼30% increase in elastic modulus and ∼12% increase in thermal conductivity have been measured in a ∼ 450 µm thick TBC after 12 h of gradient exposure. Here, the top surface of the TBC was kept at 1250 °C, and the gradient was determined based on a constant backside cooling air flow rate. The elastic modulus, measured across the thickness of coating, reveals that in the region near the top surface, the elastic modulus increased by ∼ 50%. Contrastingly, no significant increase in elastic modulus was observed near the metal/coating interface. The dynamic evolution of thermal conductivity and sintering under gradient exposure and constraint was calculated using an analytical model which was then used to rationalize the experimental observations.